The effect of a number of quantitative traits on seed productivity of alfalfa samples - К. N. Goryunov (Зерновое хозяйство России, 2020)
The current paper has presented the correlation between alfalfa seed productivity and the values of morphological characteristics for a three-year growing cycle. The purpose of the study was to estimate the correlation between the alfalfa samples' productivity and the elements of its structure and other traits in order to find their optimal values. The study was carried out in 2017-2019 on the experimental plots of the Agricultural Research Center “Donskoy”. The material for the research was a working collection of 105 alfalfa samples, varieties and lines, and the standard variety ‘Rostovskaya 90'. The crops were sown in row, in double repetition, with row spacing of 20 cm on a plot of 1m2, the seeding rate was 2 g/m2. The seed productivity of the collection samples varied from 27.2 g/m2 (the sample ‘SGP-128') to 101.0 g/m2 (the sample ‘SGP-414'). The average productivity of the standard variety ‘Rostovskaya 90' was 53.2 g/m2. About 23% of the samples that exceeded the standard variety produced 60-101 g/m2. Analysis of the graphs of the correlation between productivity and other traits made it possible to determine their optimal values, namely height of alfalfa plants varied from 80.3 (‘SPCh-434') to 107.3 cm (‘SGP-414'). The optimum plant height was between 94 and 98 cm. The number of beans per bunch in the studied samples varied from 8.8 to 16.2 pcs.; the optimal number of beans per bunch was from 12 to 13 pcs.; the number of turns on a bean was from 1.4 to 2.8, the optimal number was 2.4-2.6. The number of seeds in a bean varied on average from 3.1 to 6.4 pcs., the optimal number was 5.0-5.5 pcs. These values have formed the basis for the model of the alfalfa variety. The study of the alfalfa collection resulted in the identification several samples due to their productive and economically valuable traits.